The Impact of Obesity on Back and Core Muscular Endurance in Firefighters - John M. Mayer; James L. Nuzzo; Ren Chen; William S. Quillen; Joe L. Verna; Rebecca Miro; Simon Dagenais (Journal of Obesity)
The purpose of this study was to assess the relationships between obesity and measures of back and core muscular endurance in firefighters. Methods. A cross-sectional study was conducted in career firefighters without low back pain. Obesity measures included body mass index (BMI) and body fat percentage assessed with air displacement plethysmography. Muscular endurance was assessed with the Modified Biering Sorensen (back) and Plank (core) tests. Relationships were explored using t-tests and regression analyses. Results. Of the 83 participants enrolled, 24 (29%) were obese (BMI ≥ 30). Back and core muscular endurance was 27% lower for obese participants. Significant negative correlations were observed for BMI and body fat percentage with back and core endurance (r = −0.42 to −0.52). Stepwise regression models including one obesity measure (BMI, body fat percentage, and fat mass/fat-free mass), along with age and self-reported physical exercise, accounted for 17–19% of the variance in back muscular endurance and 29–37% of the variance in core muscular endurance. Conclusions. Obesity is associated with reduced back and core muscular endurance in firefighters, which may increase the risk of musculoskeletal injuries. Obesity should be considered along with back and core muscular endurance when designing exercise programs for back pain prevention in firefighters.